[Mrs. Mihály Polcsán 5]
1966 neon-signs at night, christmas tree, Elizabeth-bridge&Gellért mountain in winter, 1962 traffic on the streets of Budapest. 1964 opening of the Elizabeth bridge, old photos from 1876, Matthias church, 1962 Fisherman's Bastion & the town, brass band, the house fo Parlament